Specific transcriptional activation in vitro by the herpes simplex virus protein VP16. - Arnosti, D N (1993)
The herpes simplex virus protein VP16 interacts with cellular factors, including the protein Oct-1, to activate viral immediate early (IE) gene transcription. We have reproduced this effect by addition of purified, full-length VP16 and the DNA-binding 'POU' domain of Oct-1 (Oct-1/POU) to a HeLa cell in vitro transcription system. Stimulation of transcription was dependent on the IE-specific element, TAATGARAT. In agreement with earlier observations from electrophoretic mobility shift assays, activation was not observed when Oct-2/POU, the DNA-binding domain from the Oct-2 protein, was substituted for Oct-1/POU. Single round transcription assays revealed that, together, VP16 and Oct-1/POU facilitate the assembly of pre-initiation complexes at target gene promoters.